Mucocele of appendix: a case report - Fareeha Farooqui; Sehrish Latif; Humera Naz Altaf; Sania Waseem; Sohaib Khan; Muhammad Amir (Journal of the Pakistan Medical Association, 2021)
Mucinous cystadenoma is a rare tumor of appendix it accounts for only 0.4% of the gastrointestinal tract malignancies and is reported rarely in literature. Therefore the surgical management is not yet established. Here we report a case of a 65 year old female who presented with a dragging sensation and a feeling of mass in right iliac fossa. Her computed tomography (CT) suggested an abscess formation of the parietal peritoneum. She was planned for laparotomy and upon exploration a mass was found arising from tip of retroperitoneal appendix. Whole of the appendix was studded with mucoid material. Limited right hemicolectomy was performed and histopathology of appendix showed mucinous cystadenoma with no evidence of malignant changes. Patient remained uneventful and was discharged on 4th post operative day. The unusual presentation of retroperitoneal pseudomyxoma without any intraperitoneal pathology, prompted us to report this case. Continuous...